Detection of blaTEM Gene of Klebsiella pneumoniae Isolated from Swab of Food-Producing Animals in East Java - M. H. Effendi; I. G. Bintari; E. B. Aksono; I. P. Hermawan (Faculty of Animal Science, Bogor Agricultural University, 2018)
Klebsiella pneumoniae is one of 9 bacteria resistance to antibiotics in concern. This research aimed to detect any gene of blaTEM in bacteria of the K. pneumoniae isolated from swab of food-producing animals. In this study, 195 swab samples were taken from 17 sampling locations. Samples obtained were cultivated on selective medium and had several tests including identification, antibiotic sensitivity test using Kirby-Bauer method against antibiotics of ampicillin, cefotaxime, amoxicillin, meropenem, and trimetrophrim-sulfamethoxazole, and followed by PCR test for detecting the gene that was responsible for the antibiotic resistances. The results showed that 10 out of 195 samples were found to be K. pneumonia, those were 4 samples originated from dairy cows (SP-S1, SP-S3, SP-B2, SP-G4), 2 samples originated from beef (SPT-K1, SPT-K2), 1 sample originated from chickens (A-W5), and 3 samples originated from fish (IN-P2, IN-P3, IN-S3). Most of isolates (9/10) were found to be resistant toward amoxicillin. These isolates were SP-S3, SP-B2, SP-G4, SPT-KI, SPT-K2, A-W5, IN-P2, IN-P3, and the IN-S3 and all of them also showed to be positive of blaTEM gene. It could be concluded that most of K. pneumoniae isolates from food animals harbour had Extended Spectrum Beta-Lactamase (ESBL) encoding gene.